Open Your Eyes Wider: Overexposure in Contemporary American Film and TV Series - Monica Michlin (Sillages Critiques)
This article examines overexposure in contemporary film as a reflexive sign of exposure to extreme states of being. While there are realistic uses of excessive lighting in film, overexposure almost always appears symbolic, and operates as a cinematic code that translates exposure to the magical, supernatural, or unconscious “other.” Because it is so often connected to the aesthetics of shock and revelation, overexposure often plays on the limits of what we can bear to watch. Finally, although as a technique, it plays on the hypnotic attractions of excessive light, it also points to the artifice of lighting and acts as a reflexive sign that what we are gazing upon is unreal, in a contemporary enactment of the baroque allegories of life-as-dream.